Subcutaneous Injection of Bee Venom in Wistar Rats: effects on blood cells and biochemical parameters - Yaser Yousefpoor; Mahmoud Osanloo; Mohamad Javad Mirzaei-Parsa; Mohammad Reza Hoseini Najafabadi; Seyyed Mohammad Hashemi; Mitra Abbasifard (Korean Pharmacopuncture Institute, 2022)
Objectives: Bee venom (BV) therapy is performed by a bee sting or subcutaneous injection of BV. However, there is not much information on the effect of BV on blood parameters after entering the body. This project aimed to assess the side effects of subcutaneous BV injections in healthy rats by measuring the hematological and biochemical parameters.Methods : Various amounts of BV, including 100, 200, and 500 (μg/day), were subcutaneously injected into rats for 30 days. The results showed that BV affected the metabolism of the liver, kidney, and glands.Results : An increase in blood sugar and a decrease in other biochemical parameters, including cholesterol, triglyceride, urea, creatinine AST, ALT, ALP, and phosphorous, were observed. Results : also showed increased counts of white blood cells, neutrophils (%), and platelets and decreased levels of red cells, hemoglobin, and hematocrit.Conclusion : This study demonstrates that BV therapy in medical clinics requires routine care and testing to prevent eventual metabolic and anemia side effects.